Illuminance uniformity in obstructed LED surgical lighting. (December 2022) - Zhou, H; Ding, R; Qin, J; Pan, Y; Wang, M
Uniform illumination is key to surgery. According to the standard, the illuminance uniformity is measured with no obstruction, which cannot fully reflect the performance in the working environment. This study aimed to measure the illuminance uniformity with obstruction. Besides, the illuminance attenuation dispersion rate was introduced. The illuminance uniformity test was set up under the IEC Standard, and five different types of luminaires were measured. The appropriate sizes of the light spots were chosen first. Subsequently, the light sources with light field diameters d50 and d10 with or without obstacles were measured, and the illuminance attenuation dispersion rate was calculated. The experimental results showed that the d50 /d10 ratio did not appear to be affected by obstructions. There appeared visible deformation of the light spot shape in some products. As we assumed, there were significant differences in the illuminance attenuation dispersion rate among these products. Although d50 /d10 ratio did not seem to be affected by the obstructions, the shape of the light spot deformed. The illuminance attenuation dispersion rate may be a key parameter to judge the LED surgical lighting.